Gene Therapy: Carbon‐Dot‐Based Two‐Photon Visible Nanocarriers for Safe and Highly Efficient Delivery of siRNA and DNA (Adv. Healthcare Mater. 8/2014). Issue 8 (August 2014) - Wang, Liqin; Wang, Xiaoyong; Bhirde, Ashwinkumar; Cao, Jianbo; Zeng, Yun; Huang, Xinglu; Sun, Yaping; Liu, Gang; Chen, Xiaoyuan
<x xml:space="preserve">Abstract</x> X. Chen, G. Liu, and co‐workers develop photoluminescent carbon dots (Cdot) by using low molecular weight amphiphilic polyethylenimine for surface passivation, which possesses low cytotoxicity, good stability, monodispersity with narrow size distribution, high gene delivery efficiency, and fluorescence performance. The Cdot formula introduced on page 1203 serves as a novel imaging‐trackable gene‐delivery na nocarrier promising for gene therapy and optical molecular imaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>